“Cricket Has Given Me Everything”: Women’s Sport and the Women’s Movement in Twentieth-century Britain - Rafaelle Nicholson (Revue Française de Civilisation Britannique)
This article examines the formation of the governing body of women’s cricket in 1926 and its subsequent activities, arguing for a reinsertion of women’s sport into the history of women and the women’s movement in twentieth-century Britain. The centrality of sport to many women’s lives is clearly demonstrated; it is argued that playing cricket was a way to challenge discourses surrounding female frailty, and a way for women to reject traditional models of domesticity, placing their own leisure needs above servicing the needs of their husbands. Overall it is suggested that a detailed examination of women’s sporting lives can disrupt and alter our current understanding of women’s history, revealing new continuities in the ideological development of the women's movement. Including sporting organisations in a broader definition of the women’s movement is therefore crucial for historians, as we seek to make sense of women’s lives across the twentieth century.